Spectrum of antibiotic resistance in UTI caused by Escherichia coli among HIV-infected patients in Uganda: a cross-sectional study - George Abongomera (BMC, 2021)
Abstract Background Antimicrobial drug resistance is one of the top ten threats to global health according to the World Health Organization. Urinary tract infections (UTIs) are among the most common bacterial infections and main reason for antibiotic prescription. The incidence of UTIs appears to be high among people living with HIV. We sought to determine the most common UTI pathogens among HIV infected patients and evaluate their susceptibility towards antibiotics. Methods We performed a cross-sectional study among HIV-infected patients aged ≥ 18 years presenting at an HIV care specialized clinic with symptoms suggestive of a urethritis. Urine cultures were subjected to antibiotic susceptibility testing according to Clinical Laboratory Standards Institute. The data was analyzed using STATA, we performed Pearson’s Chi-square and Fisher’s exact tests to compare differences between proportions. Results Out of the 200 patients, 123 (62%) were female. The median age was 41.9 years (IQR 34.7–49.3). Only 32 (16%) urine cultures showed bacterial growth. Escherichia coli was the most commonly isolated uropathogen (72%), followed by Klebsiella pneumoniae (9%). E. coli was completely resistant to cotrimoxazole and ampicillin; resistance to ciprofloxacin and ceftriaxone was 44% and 35% respectively; 9% to gentamicin; no resistance detected to nitrofurantoin and imipenem. Conclusions Our findings are congruent with the Uganda national clinical guidelines which recommends nitrofurantoin as the first line antibiotic for uncomplicated UTI. Significant ciprofloxacin and ceftriaxone resistance was detected. In the era of emerging antibiotic resistance, understanding the local susceptibilities among sub-populations such as HIV infected patients is crucial. Further investigation is needed to address reasons for the low bacterial growth rate observed in the urine cultures.